2021
DOI: 10.4103/jpgm.jpgm_1018_20
|View full text |Cite
|
Sign up to set email alerts
|

The association of plasma acyl ghrelin level with alcohol craving in early abstinent alcohol dependent patients

Abstract: Background: Craving plays an important role in maintenance of alcohol dependence. Earlier studies have analyzed the role of ghrelin in craving and their results have been heterogenous. Acyl ghrelin is its more active form as it crosses the blood brain barrier. Hence we aimed to examine the relationship between plasma acyl ghrelin and craving in Indian patients having alcohol dependence syndrome. Methods: The present study was a hospital-based prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Firstly, some, mainly earlier, plasma-association studies measured only total ghrelin and did not consider active acylated ghrelin. As previously mentioned, studies have shown associations between AUD and acylated, rather than total ghrelin (Koopmann et al, 2012 , 2019 ; Sha et al, 2021 ). Secondly, the so-called inactive form of ghrelin, des-acyl-ghrelin, may have other functions than just being inactive and thus have its own implications for addiction (Delhanty et al, 2014 ; Ardeshiripur et al, 2018 ).…”
Section: Appetite-regulatory Peptides In Substance Use Disordermentioning
confidence: 86%
See 1 more Smart Citation
“…Firstly, some, mainly earlier, plasma-association studies measured only total ghrelin and did not consider active acylated ghrelin. As previously mentioned, studies have shown associations between AUD and acylated, rather than total ghrelin (Koopmann et al, 2012 , 2019 ; Sha et al, 2021 ). Secondly, the so-called inactive form of ghrelin, des-acyl-ghrelin, may have other functions than just being inactive and thus have its own implications for addiction (Delhanty et al, 2014 ; Ardeshiripur et al, 2018 ).…”
Section: Appetite-regulatory Peptides In Substance Use Disordermentioning
confidence: 86%
“…Nevertheless, plasma ghrelin has been positively associated with higher alcohol craving in abstaining AUD patients (Addolorato et al, 2006 ; Wurst et al, 2007 ; Leggio et al, 2012 ). Taking into account that ghrelin can be in both acylated, traditionally called the active, and des-acylated forms, more recent studies have shown that acylated, rather than total, plasma ghrelin was associated with alcohol craving (Koopmann et al, 2012 , 2019 ; Sha et al, 2021 ). Furthermore, functional magnetic resonance imaging studies have demonstrated a positive correlation between active plasma ghrelin and neuronal alcohol-cue reactivity (Bach et al, 2019 ; Koopmann et al, 2019 ).…”
Section: Appetite-regulatory Peptides In Substance Use Disordermentioning
confidence: 99%
“…[ 97 220 221 222 223 224 225 226 ] A few studies explored the role of biological markers (leptin, ghrelin) as predictors of relapse. [ 227 228 ] Interpersonal factors, social support, and occupational factors emerged as being associated with abstinence. [ 220 229 230 231 ] Treatment-related factors like retention to treatment and being on regular medications predicted treatment outcomes, including abstinence.…”
Section: Course and Prognosismentioning
confidence: 99%